Novel water- and fertilizer-management strategy: Nutrient-water carrier. (1st April 2021) - Wang, Jinpeng; Chen, Huiyu; Ma, Ronghui; Shao, Junfei; Huang, Songjun; Liu, Yan; Jiang, Yuanmao; Cheng, Dongdong
Abstract: A novel water- and fertilizer-management strategy has been developed in the study, which was called nutrient-water carrier. The nutrient-water carrier (NC) was prepared from N, O-carboxymethyl chitosan (NOCMC), acrylic acid (AA) and polyphosphate urea (PDUP) by solution polymerization. The nutrients content of NC was more than 70%, and it showed excellent water-retention and slow-released capacity properties. The optimal superabsorbent sample with excellent water absorbency (791.26 g/g) was obtained under the condition: 75% of AA neutralized, 10 wt% NOCMC, 5 wt% PDUP, 0.6 wt% APS, 0.05% MBA to AA weight, reaction at 70 °C for 2.0 h. After loading 25 wt% PDUP to AA weight into the polymer network, the swelling degree (SD) of optimal NC arrived 482.59 g/g. FTIR, SEM, EDS and TG were used to characterize the structure and performance of optimal NC. Results illustrated that the semi-interpenetrate structure (semi-IPN) was constructed by the incorporation of linear PUDUP into the superabsorbent network, and the NC could dramatically enhance the water holding capacity of sandy loam, six-folders than without NC. In addition, the application of NC in sandy loam soil had a positive synergistic effect on the root length and seedling height of maize. Furthermore, the slow-released behavior for N, P and K was investigated. All the facts indicated that the NC could improve nutrients-efficiency, prolong the period of fertilizer release, decrease irrigation frequency and address environmental pollution, which was expected to be widely used in semi-arid and arid areas. Graphical abstract: Image 1